Pendekatan Ekologi Integral Untuk Mengatasi Krisis Lingkungan Hidup Menurut Paus Fransiskus - Wenehenubun , Maria Helena (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2025)
This research aims to understand the concept of integral ecology according to Pope Francis as a solution to the escalating global environmental crisis. Pope Francis, in his encyclical Laudato Si’, calls humanity to adopt an ecological perspective that unites environmental, social, cultural, and spiritual dimensions for the common good. Using a qualitative-descriptive approach, this study examines literatures and related documents on Pope Francis’ view, especially as outlined in Laudato Si’. This approach is applied to understand the core principles of integral ecology, including the balance between humans and nature, collective responsibility, and intergenerational justice. The study reveals that integral ecology offers a holistic perspective encompassing various aspects of life, requiring the involvement of all societal elements, both individuals, communities, and nations, to contribute to environmental preservation. This concept also emphasizes the importance of ethical and spiritual aspects in fostering a healthy relationship between humanity and nature.